Successful Implementation of an Alcohol Screening, Brief Intervention, and Referral to Treatment Program. Issue 3 (May 2018) - Zimmermann, Eric; Sample, Jason M.; Zimmermann, Mary Ellen; Sullivan, Francesca; Stankiewicz, Sarah; Saldinger, Pierre
Abstract : Devastating effects of alcohol are well established in trauma. To address this, thve American College of Surgeons Committee on Trauma (ACS-COT) requires ACS-verified Level 1 trauma centers to have an active screening, brief intervention, and referral to treatment (SBIRT) program. In 2015, NewYork-Presbyterian/Queens successfully implemented an SBIRT program. Previous studies indicate difficulty in achieving a high level of SBIRT compliance. We explored the effects of a multidisciplinary approach in implementing a standardized screening protocol for every trauma-activated patient 15 years or older. A multidisciplinary team developed a standardized approach to identifying trauma patients for our SBIRT program. Social workers were trained in performing brief interventions and referral to treatment at a New York State-level training course prior to starting our SBIRT program. Blood alcohol levels were obtained in every trauma activation. Trauma patients who had a blood alcohol level greater than 0.02% were identified and tracked by the trauma service. These patients were referred to social workers, underwent brief intervention, and evaluated for referral to treatment if determined to be a high-risk alcohol user. Over the 8-month implementation period, we evaluated 693 trauma patients. A blood alcohol level was obtained on most trauma patients ( n = 601, 86.6%). Patients with a blood alcohol level greater than 0.02% were referred to a social worker ( n = 157, 22.6%). Social workers performed a brief intervention and evaluation for referral/treatment services for 129 of the trauma patients with elevated blood alcohol levels. Overall, 82% of intoxicated trauma patients underwent brief intervention, which identified 22 patients who were referred for treatment programs. An inclusive multidisciplinary approach to the implementation of an SBIRT program achieves a high level of compliance.